Experiences of Unknowing: This Is Not (Only) a Clay Vessel - Victoria Rodriguez Schon (DIID, 2024)
This study explores unlearning as reflexivity, challenging traditional knowledge through clay work and weaving with Wichí masters in Salta, Argentina. Making became a method to enter liminal spaces, connecting master and student while unlearning linear ways of seeing the world, time, and design. This revealed tacit knowledge that emerges through creation, transforming design into an act of unknowing and opening to knowledge that resided within the piece of clay in my hands.